Inglis tilin oqıtıwda jergilikli mádeniyat (Desi - Rayan hám Gardnerdiń motivaciya teoriyaları mısalında) - Orazımbetov, Sh.Á (SCIENCE and SOCIETY, 2025)
The article analyzes the importance of motivation in learning English and some motivational theories. Conclusions were drawn made on research conducted worldwide on motivation and its types. The indicated theories are considered using the example of students’ local culture, and the author provides methodological recommendations for their adaptation.
Keywords: Gardner’s motivation theory; motivation; integrative motivation; instrumental motivation; intrinsic motiva- tion; extrinsic motivation; Self-Determination Theory